Wound healing effects of 80% methanol and solvent fractions of the leaf of Cordia Africana Lam: (Boraginaceae) against wound models in mice - Jemal Abdela; Fuad Adem; Ahmedmenewer Abdu; Mohammed Yusuf; Abenezer Aklog Wondimu; Mohammed Abdurke Kure; Mekonnen Sisay; Burka Mohammedsani; Monas Kitessa; Abraham Nigussie Mekuria (PLoS ONE, 2025)
Background Chronic wounds present a major health challenge, and traditional remedies are frequently employed in developing nations for wound treatment. This study sought to assess the safety and effectiveness of various solvent extracts from Cordia africana using excision and incision wound models in mice. Methods The dried, coarsely ground 500 g of plant leaves were separately macerated three times with 80% methanol, absolute methanol, chloroform, and aqueous water. Acute dermal toxicity was assessed by applying 2000 mg/kg of the 10% w/w of the solvent extracts. In both wound models, animals were randomly divided into four groups of five mice each. Group I received a simple ointment and served as the negative control. Group IV was treated with nitrofurazone (0.2%) ointment as the positive control. Groups II and III were treated with 5% w/w and 10% w/w ointments of the solvent extracts, respectively. Results The acute dermal toxicity studies demonstrated that the plant leaf extracts are safe, as there were no signs of toxicity observed. In the excision wound model, the application of 5% and 10% ointments of the 80% methanol extract resulted in significant (p < 0.05) wound contraction compared to the negative control group, starting from day 13 and day 5, respectively. Similarly, 10% ointments of both absolute methanol and chloroform extracts significantly (p < 0.05) reduced wound size starting from day 7. Furthermore, the time required for complete epithelization was significantly shorter (p < 0.05) for the 80% methanol, chloroform, and absolute methanol extracts compared to the negative control. The chloroform fraction and 10% ointment of the 80% methanol extracts also significantly increased hydroxylproline content. The 5% and 10% chloroform extract ointments (66.02% and 72.20%, respectively) and the 10% ointment with an 80% methanol extract (55.49%) significantly improved the tensile strength of the mice skin (p < 0.05) compared to the group treated with a simple ointment (1.6%). Conclusion The study revealed that Cordia africana leaf extracts possess significant wound-healing properties, supporting its traditional medicinal use. It was found that using less polar solvents is more effective in extracting components with enhanced wound-healing effects.